The Interferences Faced by The EFL Students in Listening Comprehension - Isnaeni Wahab; Novalia Tanasy (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2022)
Listening is one of the important skills which must be possessed by the students. But, unfortunately, some students can not cover it in their learning. They found some difficulties during listening. This research aimed to find out the interferences that are faced by the EFL students. This research was qualitative descriptive research. The data is collected from the questionnaires to get the information on students’ difficulties. The data showed that some factors interrupt the learners in listening and they came from internal and external factors. The existing difficulties mostly come from the material given, the second factor comes from the listener and the last factor is related to the physical setting. It is correct that the interferences in listening comprehension faced by students, not only from the listeners themselves but also from content material and surroundings during the listening process. Hence, the students have to find the appropriate way and practice more to improve their listening ability. Keywords: Listening Comprehension, Difficulties, EFL Students